Gender Stereotypes Portrayed in Five Most Popular Indonesian Folktales: Literature in ELT - Sari, Alfia; Sueb, Sueb; Anugerahwati, Mirjam (E-Structural (English Studies on Translation, Culture, Literature, and Linguistics), 2024)
Folktales have been a medium through which children can transfer knowledge, language, and cultural values at an early age. The existence of folktales cannot be separated from the values prevalent in society. Numerous moral principles are sound for life. As literary works for learning, folktales should introduce gender roles. However, some local cultures and ideologies can represent the role of gender in some areas. Therefore, this study investigates the gender stereotypes in the five most popular Indonesian folktales: Roro Jonggrang, Timun Mas, The Legend of Malin Kundang, The Origin of Lake Toba, and Bawang Merah Bawang Putih. These stories were chosen because they are the most searchable folktales online and are the most used as learning materials in Indonesian school textbooks: English for Nusantara and When English Rings a Bell. Critical discourse analysis (CDA) analyzes the relationship between discourse language and other semiotic cues. The results revealed two aspects of each character's social and domestic roles. The male characters dominate the stories, where male characters are depicted as people who work, travel, and fight. In contrast, female characters are depicted as housewives who do all the housework. This showed a patriarchal culture is involved in the stories, which impacts the portrayal of men and women in society. Therefore, gender construction in these five most popular folktales is needed as they are used as learning materials to teach values to young learners.